Expanders, Group Extensions, Hadamard Manifolds and Certain Banach Spaces (Communications in Mathematical Research, 2019)
In this note, we prove that expanders cannot be coarsely embeddedinto group extensions of sequences of groups which are coarsely embeddable intoHardamad manifolds and certain Banach spaces due to the similar concentrationtheorems.